A preliminary investigation of schedule parameters on cocaine abstinence in contingency management. Issue 1 (10th May 2022) - Regnier, Sean D.; Strickland, Justin C.; Stoops, William W.
Abstract : Contingency management (CM) interventions are the most effective psychosocial interventions for substance use disorders. However, further investigation is needed to create the most robust intervention possible. This study investigated the effects of 1) reinforcer magnitude; and 2) fixed and escalating and resetting incentives on cocaine abstinence in an outpatient trial. In this analysis, 34 treatment‐seeking individuals with Cocaine Use Disorder received either high or low value incentives for providing a benzoylecgonine‐negative urine sample or were in a control condition and received incentives for providing a urine sample regardless of the results. Participants received either escalating and resetting incentives, wherein the value of each incentive increased with consecutive negative samples and reset to the initial level upon a positive sample (Experiment 1), or fixed incentives, wherein they received the same value incentive for each negative urine sample they provided (Experiment 2). Large incentives produced more abstinence, although escalating and resetting reinforcer values did not have a differential effect. Large, fixed incentives promoted abstinence faster than other reinforcers, whereas smaller incentives resulted in poor abstinence and took many visits to achieve initial abstinence. Future research comparing different schedules on cocaine abstinence in a randomized control trial with a larger sample size is required.